PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. TIRTA SARI SURYA RENGAT - Lisa Haryati; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
An important problem faced by companies is how to maintain employee morale so that they can provide maximum performance or performance. Strive to maintain employee morale is one of the company's goals. This research was conducted at PT. Tirta Sari Surya Rengat. The purpose of this study was to determine the effect of participatory leadership style and work environment on employee morale at PT. Tirta Sari Surya Rengat. Participative leadership style and work environment as independent variables (X1, X2) while employee morale as the dependent variable (Y).The problem in this study is the occurrence of fluctuating employee turnover and entry. It can be seen from the company's Labor Turnover data. The sample of this research was taken as many as 60 respondents and the technique used was census. The data obtained from the results of the questionnaire and then processed and then tested statistically through the SPSS program.From the results of the tests conducted, it shows that the participatory leadership style and work environment have a positive and significant effect on employee morale at PT. Tirta Sari Surya Rengat.Keywords: Participatory Leadership Style, Work Environment, and Employee Work Spirit.